Don’t Stand Up in a Hammock: Advice from Early Career Teachers in Remote, Regional and Rural Locations - Willis, Alison; Louth, Sharon (Australian and International Journal of Rural Education, 2024)
This ethnographic case study investigates the professional, locational and cultural understandings teachers need when beginning regional, rural, and remote teaching and living. Drawing from the experiences of recently graduated early career teachers in regional, rural, and remote teaching positions, the study sought to identify key learnings and strategies for surviving and thriving in regional, rural, and remote communities with the aim of better preparing pre-service teachers for placements and future employment in these locations. Most early career teachers in this study would recommend regional, rural, and remote teaching positions to pre-service teachers, describing the experience as rewarding, challenging and professionally developing. The importance of building relationships and immersing oneself in community were salient in the data. Analysis revealed a need for pre-determinations in five areas when preparing for RRR teaching positions: social (building networks and making friends), geographical (exploring the local area and getting involved in community), emotional (positive mindset and getting out of your comfort zone), personal (healthy habits and resilience), and cultural (understanding community). There is an evident opportunity to help pre-service teachers prepare for regional, rural, and remote experiences by considering these five pre-determinations.